Модернизация поршневой группы дизеля K6S310DR - Белогуб, Александр Витальевич; Пылев, Владимир Александрович; Бодяко, Александр Михайлович; Галагаев, Сергей Викторович; Бодяко, Андрей Александрович (НТУ "ХПИ", 2013)
The paper considers the possibility and the results of current research on the modification of the piston and piston rings which are related to a decreasing of their number and size. The identification of thermal boundary conditions of the existing structure was carried out and modified side surface profile was calculated. It is shown that the implementation effect will be in reducing of the friction losses in cylinder-piston group and improving of the lubrication conditions on pair skirt-cylinder glass. It will increase the lifecycle of the engine and reduce fuel consumption.

В работе рассмотрена возможность и результаты расчетного исследования по изменению конструкции поршня и поршневых колец, связанного с уменьшением их количества и размеров. Проведена идентификация тепловых граничных условий имеющейся конструкции и рассчитан модифицированный профиль боковой по- верхности. Показано, что эффект от внедрения предложения будет состоять в снижении потерь трения в цилиндропоршневой группе и улучшении условий смазки пары тронк – зеркало цилиндра, что повысит ресурс двигателя и снизит расход топлива.
Modernization of the piston group’s of the diesel engine K6S310DR
Keywords: тепловозы; конструкция дизеля; поршневые комплекты; непрерывно-циклическое литье нагораживанием; направленное затвердевание